Systematizing Source Management and Citation in Academic Writing Using EndNote: My Lived Experience - Sharma, Uma N. (Studies in ELT and Applied Linguistics, 2025)
It is assumed that a reference management software, such as EndNote, systematizes the intricate process of source management and citation in academic writing by providing users with the ability to construct personalized digital libraries. This paper explores the validity of this postulation, specifically within the context of the American Psychological Association (APA) 7th style of citation, focusing on the EndNote software programme. Drawing on my firsthand experience with EndNote X9 and my responsibility for instructing master’s degree students, as well as MPhil and PhD scholars in the utilization of the software, I have reflected on the software’s remarkable features as the evidence of how the proper use of EndNote systematize citations in academic writing. Through practical examples, I have elucidated how EndNote facilitates the systematic citation of sources in academic writing. Based on the overall findings, it is evident that EndNote, when utilized to its full potential, effectively systematizes citations in academic writing. This enables researchers to redirect their focus to the core aspects of their work—conducting and disseminating research through report writing. In essence, EndNote becomes a tool that empowers researchers to concentrate on substantive contributions, emphasizing the significance of efficient source management in scholarly endeavors.